Host-feeding patterns of mosquito species in Germany - Börstler, Jessica; Jöst, Hanna; Garms, Rolf; Krüger, Andreas; Tannich, Egbert; Becker, Norbert; Schmidt-Chanasit, Jonas; Lühken, Renke (Parasites & vectors, 2016)
Mosquito-borne pathogens are of growing importance in many countries of Europe including Germany. At the same time, the transmission cycles of most mosquito-borne pathogens (e.g. viruses or filarial parasites) are not completely understood. There is especially a lack of knowledge about the vector capacity of the different mosquito species, which is strongly influenced by their host-feeding patterns. While this kind of information is important to identify the relevant vector species, e.g. to direct efficient control measures, studies about the host-feeding patterns of mosquito species in Germany are scarce and outdated.